Promenaders strolling along the Charles River Embankment in Back Bay, ca. 1912 - Unknown (Tufts Archival Research Center, 2005)
Street-level view northeast of promenaders strolling along the Charles River Embankment in the Back Bay. The embankment is located between the Charles River to the west and Beacon Street to the east. Street lights line the embankment. The northeast elevations of houses lining Beacon Street are visible in the center-right half of the photograph. Beacon Hill, including the dome of the Massachusetts State House, is visible in the background of the photograph, to the northeast of the Back Bay and the Charles River Embankment. The Esplanade replaces the Charles River Embankment in 1931 with funds donated by James J. Storrow 8 x 9 15/16 Photographs